Challenges of Implementing Service-Learning Pedagogy In Nigeria Public Universities - et. al., Lillian I.Olagoke-Oladokun (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Service-learning is a form of experiential learning that enables students to apply the knowledge acquired in the classroom towards the development of their immediate environment. Service-learning as experiential learning advocates active learning contrary to the passive form of learning associated with the traditional method of teaching and learning in most Nigerian public universities. This study explores the challenges encountered by students in Nigeria public universities during service-learning implementation. Participants: Students and faculty members were interviewed to generate information from their life experiences of service-learning implementation. The data gathered using semi-structured interview questions were transcribed and coded using the NVIVO software to generate themes. Findings showed inadequate time, inadequate knowledge of implementation, lack of funds, lack of co-operation among students during the implementation, inadequate supervision, and a structured guideline for service-learning implementation and logistics as the major challenges associated with adopting service-learning as a form of learning in Nigeria public universities